Map of industrial activity in Maysan Governorate using geographic information systems (GIS) (Journal of Misan Researches, 2022)
Maysan Governorate enjoys enormous natural and human resources as well as its strategic location. Industry constitutes a cornerstone of its economic activity. However, it has not received the same degree of interest from cartologists, as there is great difficulty in providing detailed industrial data and information, and for this reason, industrial activity maps were drawn in the province in line with the level of information available and its importance. Industrial facilities can be classified according to the size of the industry into three categories, small, medium and large industrial facilities, as there are small and large industrial facilities in the Maysan governorate and devoid of medium industrial facilities according to industrial statistics obtained by the researcher until 2020.